Host determinants of infectiousness in smear-positive patients with pulmonary tuberculosis - Acuña-Villaorduña, Carlos (2019)
Background Epidemiologic data suggests that only a minority of tuberculosis (TB) patients are infectious. Cough aerosol sampling is a novel quantitative method to measure TB infectiousness. Methods We analyzed data from three studies conducted in Uganda and Brazil over a 13-year period. We included sputum acid fast bacilli (AFB) and culture positive pulmonary TB patients and used a cough aerosol sampling system (CASS) to measure the number of colony-forming units (CFU) of Mycobacterium tuberculosis in cough-generated aerosols as a measure for infectiousness. Aerosol data was categorized as: aerosol negative (CFU = 0) and aerosol positive (CFU > 0). Logistic regression models were built to identify factors associated with aerosol positivity. Results M. tuberculosis was isolated by culture from cough aerosols in 100/233 (43%) TB patients. In an unadjusted analysis, aerosol positivity was associated with fewer days of antituberculous therapy before CASS sampling (p = .0001), higher sputum AFB smear grade (p = .01), shorter days to positivity in liquid culture media (p = .02), and larger sputum volume (p = .03). In an adjusted analysis, only fewer days of TB treatment (OR 1.47 per 1 day of therapy, 95% CI 1.16-1.89; p = .001) was associated with aerosol positivity. Conclusion Cough generated aerosols containing viable M. tuberculosis, the infectious moiety in TB, are detected in a minority of TB patients and rapidly become non-culturable after initiation of antituberculous treatment. Mechanistic studies are needed to further elucidate these findings.